2015
DOI: 10.5152/akd.2015.5791
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of Red Bull energy drink on ventricular repolarization in healthy young volunteers: a prospective study

Abstract: Objective: Energy drinks (EDs) are widely consumed products of the beverage industry and are often chosen by teenagers and young adults. Several adverse cardiovascular events and malignant cardiac arrhythmias following consumption of EDs have been reported in the literature. Several studies have suggested that the interval from the peak to the end of the electrocardiographic T wave (Tp-e) may correspond to the dispersion of repolarization and that an increased Tp-e interval and Tp-e/QT ratio are associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
29
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 28 publications
6
29
0
4
Order By: Relevance
“…In support of these studies are those that measured cardiovascular parameters for $60 min; for example, Elitok et al (37) reported an increase in heart rate and blood pressure in response to the ingestion of 355 mL sugared Red Bull at 60 and 120 min postconsumption, whereas Worthley et al (32) showed an increase in blood pressure at 60 min postconsumption of 250 mL of a sugar-free Red Bull-like drink with no change observed after carbonated water ingestion. Moreover, Steinke et al (30) showed significant increases in heart rate (+5-7 beats/min), as well as in systolic and diastolic blood pressure (+4-8 mm Hg) between 60 and 240 min postconsumption of 500 mL of an ED that was similar in composition to Red Bull.…”
Section: Eds and Hemodynamics: Discrepancies Between Studiesmentioning
confidence: 68%
“…In support of these studies are those that measured cardiovascular parameters for $60 min; for example, Elitok et al (37) reported an increase in heart rate and blood pressure in response to the ingestion of 355 mL sugared Red Bull at 60 and 120 min postconsumption, whereas Worthley et al (32) showed an increase in blood pressure at 60 min postconsumption of 250 mL of a sugar-free Red Bull-like drink with no change observed after carbonated water ingestion. Moreover, Steinke et al (30) showed significant increases in heart rate (+5-7 beats/min), as well as in systolic and diastolic blood pressure (+4-8 mm Hg) between 60 and 240 min postconsumption of 500 mL of an ED that was similar in composition to Red Bull.…”
Section: Eds and Hemodynamics: Discrepancies Between Studiesmentioning
confidence: 68%
“…It is known that several stimulants are included in formulas of different energy drinks. More credible is the argument that energy drinks affect the cardiovascular conduction system and lead to catastrophic events via lethal arrhythmias (1, 2). The aim to achieve higher levels of athletic performance and academic success leads to a gradual increase in consumption in the young population.…”
mentioning
confidence: 99%
“…In this issue of the Anatolian Journal of Cardiology, Elitok et al (8) reported on the electrocardiographic effects of Red Bull. (8) They had particular interest in Red Bull’s effects on ventricular repolarization.…”
mentioning
confidence: 99%
“…(8) They had particular interest in Red Bull’s effects on ventricular repolarization. The dispersion of ventricular repolarization (DVR), as indicated by a longer interval between the T wave’s peak and end (Tpe or Tpe/QT), correlates with arrhythmic risk in multiple populations (9-15).…”
mentioning
confidence: 99%
See 1 more Smart Citation